Introduction: The crisis in mental health and education - Williams, Emma (Journal of Philosophy of Education, 2022)
The introduction to this Policy Special Issue begins by situating the themes of mental health and education in the broader context of the public mental health conversation, and the new challenges to individual and collective life brought about by the COVID-19 pandemic. It then charts some of the ways mental health has developed in educational thinking and educational policy in recent years. Philosophy is then introduced as a form of thinking that encourages a slowing down of—and critical a standing back from—the momentum that gathers around the proliferation of talk about young people's problems in mental health in society, and the interventions designed to tackle these problems in education. What brings the contributions of this Policy Special Issue together is, it is observed, a degree of unease about current approaches to mental health in education. An overview of the contributions is then provided, which introduces the reader to the ways that philosophical thinking is brought to challenge and reconceive current ways of thinking about mental health in education in this Policy Special Issue. The five sections of the Policy Special Issue are also introduced: From clinics to classrooms; Tackling mental health in the curriculum; Sickness in society; Language in crisis; and Curing education.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1467-9752.12657
Keywords: education; humanities; mental health; philosophy; schools